Peculiarities of public regulation of real estate agent's activities - Raslanas, Saulius (Technological and Economic Development of Economy, 2005)
Recently a demand for professional real estate agents has increased in the market. The present paper includes a research into the real estate related activity of the USA and Lithuania carried out in accordance with the chosen criteria. According to real estate agency service quality research in the USA the most important factor is agents professionalism. This thesis places a major emphasis on the activity and structure of real estate agents, law on licence issue as well as advantages and disadvantages; it also presents proposals on improvement and development of real estate agents activity. Real estate licencing is necessary in order to raise the level of professionalism and qualification of real estate agents in Lithuania, to adjust relationship between property owners and middlemen, as well as to increase the level of confidence among real estate agents.Article in Lithuanian.Nekilnojamojo turto agento veiklos valstybinio reguliavimo aspektaiSantrauka. Pastaruoju metu profesionalių nekilnojamojo turto agentų poreikis rinkoje išaugo. Straipsnyje JAV ir Lietuvos nekilnojamojo turto agentų veikla analizuojama pagal pasirinktus kriterijus. Remiantis JAV nekilnojamoj o turto agentūrų paslaugų kokybės tyrimais, svarbiausias veiksnys yra agentų profesionalumas. Ši mintis akcentuojama nekilnojamojo turto agentų veikloje ir struktūroje kaip licencijavimo įstatymo problema, taip pat pabrėžiami jo privalumai ir trūkumai bei pateikiami siūlymai nekilnojamojo turto agentų veiklai tobulinti, gerinti. Norint padidinti Lietuvos nekilnojamojo turto agentų profesionalumą ir kvalifikaciją, sureguliuoti turto savininkų ir tarpininkų santykius bei padidinti pasitikėjimą nekilnojamojo turto agentais, būtina licencijuoti nekilnojamąjį turtą.Reikšminiai žodžiai: nekilnojamasis turtas, agentas, brokeris, paslaugos kokybė, licencija.First Published Online: 21 Oct 2010